2005
DOI: 10.1017/s0950268805004413
|View full text |Cite
|
Sign up to set email alerts
|

Lyme disease in France: a primary care-based prospective study

Abstract: To estimate the incidence of Lyme borreliosis in France, describe its clinical presentations, and assess its potential risk factors, we conducted a nationwide prospective study in the French Sentinelles Network, consisting of 1178 general practitioners (GPs). Of these, 875 (74%), i.e. 1.6% of all French GPs, participated in the study from May 1999 to April 2000. Eighty-six cases of Lyme disease were reported and validated, of which 77 (90%) consisted of erythema migrans. At national level, the incidence was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 23 publications
6
29
1
3
Order By: Relevance
“…A single study in Alsace revealed the presence of B. burgdorferi sensu lato in 11% of 2,223 nymphs collected in August 1989 (6). This northeastern region of France is reported as a region where LB is highly endemic (24). Moreover, a prospective study conducted in Alsace from 2001 to 2003 (18) estimated the LB incidence between 180 and 232 cases per 100,000 inhabitants per year and recorded high local variations between cantons (administrative divisions of a department in France).…”
mentioning
confidence: 99%
“…A single study in Alsace revealed the presence of B. burgdorferi sensu lato in 11% of 2,223 nymphs collected in August 1989 (6). This northeastern region of France is reported as a region where LB is highly endemic (24). Moreover, a prospective study conducted in Alsace from 2001 to 2003 (18) estimated the LB incidence between 180 and 232 cases per 100,000 inhabitants per year and recorded high local variations between cantons (administrative divisions of a department in France).…”
mentioning
confidence: 99%
“…A French national primary care-based prospective study estimated an overall national incidence rate of 9.4/100,000 (Letrilliart et al, 2005), whereas data from the Alsace study suggested a regional rate of 180-232/100,000, which varied from 30 to 511/100,000 between individual cantons in the region. Erythema migrans was the only manifestation of disease in 90% of the cases; a further 5% had evidence of neuroborreliosis.…”
Section: Regional Clinical Surveillance and Prospective Studiesmentioning
confidence: 99%
“…L'agent infectieux en cause est une bactérie spiralée de la famille des Spirochaetaceae : Borrelia burgdoferi sensu lato. La France fait partie des zones d'endémie de la maladie et l'incidence nationale a été estimée à 9,4/100 000 habitants [3], avec des variations selon les régions, les incidences les plus élevées étant dans le Limousin et surtout en Alsace (> 30/100 000 habitants) [4]. Chez l'enfant, il n'existe aucune donnée en France.…”
Section: Résuméunclassified
“…Au terme de ces différentes étapes, nous avions une réponse pour chacun des 70 pédiatres de ville du Bas-Rhin. La définition des cas de borréliose de Lyme devait correspondre aux critères Eucalb (European Union Concerted Action on Lyme Borreliosis) [3,5]. Ces critères (Tableau I) accompagnaient le questionnaire.…”
Section: Méthodesunclassified
See 1 more Smart Citation